2012
DOI: 10.1021/jp3003728
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Formation of MOF-5 Nanoparticles—A SANS Analysis

Abstract: MOF-5 nanoparticles were prepared by mixing a solution of [Zn4O(C6H5COO)6] with a solution of benzene-1,4-dicarboxylic acid in DMF at ambient conditions. The former species mimics as a secondary building unit (SBU), and the latter acts as linker. Mixing of the two solutions induced the formation of MOF-5 nanoparticles in dilute suspension. The applied conditions were identified as suitable for a closer investigation of the particle formation process by combined light and small angle neutron scattering (SANS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…[20][21][22] However, it has been shown that basic [Zn 4 6 ] can be used as a starting material to synthesize rapidly MOF-5, although it was not reported whether the [Zn 4 O] 6 + core remained intact during the synthesis process. [48,51] This set of observed heights was replicated in a second separate experiment (H) and the micrographs and height analyses are given in Figure SI Cross-sectional analyses of growing step edges provide some insight into the growth mechanism of the surface monolayer terraces and the relative rates of spreading of the 0.85 nm and 0.45 nm sub-layers making up the complete monolayer. Detailed measurements of the lateral dimensions of several growing step edges of MOF-5 were taken.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] However, it has been shown that basic [Zn 4 6 ] can be used as a starting material to synthesize rapidly MOF-5, although it was not reported whether the [Zn 4 O] 6 + core remained intact during the synthesis process. [48,51] This set of observed heights was replicated in a second separate experiment (H) and the micrographs and height analyses are given in Figure SI Cross-sectional analyses of growing step edges provide some insight into the growth mechanism of the surface monolayer terraces and the relative rates of spreading of the 0.85 nm and 0.45 nm sub-layers making up the complete monolayer. Detailed measurements of the lateral dimensions of several growing step edges of MOF-5 were taken.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, relatively little has been reported on the actual crystallization process of MOF‐5,46, 47 particularly with regard to the actual growth of the MOF‐5 crystallites themselves during the stages of nucleation and crystal growth 32. 48…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Figure 2 shows AFM deflection images taken from experiment A in Table 1. This experiment was started by introducing a standard growth solution (SA-1, Table 1) with a Zn/H 2 BDC > 1 over the MOF-5 seed crystals to induce MOF-5 growth.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was found that modulation slowed down both the initial formation of MOF particles and their growth rate, but had no effect on nal particle size compared to unmodulated syntheses. 37 This suggests inhibition either through competitive metal coordination or pH control, but a follow-up study from the same group where the 4-decylbenzoic acid modulator was added in a larger excess 5 minutes aer the initial mixing of the reagents allowed identication of the modulator at crystallite surfaces by SANS. This was feasible by determining an appropriate mixture of deuterated and protonated DMF solvent which matched the neutron scattering contrast of MOF-5, and therefore allowing scattering by the large alkyl chains of the modulator to be identied.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%